Gut yeast diversity of Helicoverpa armigera (Lepidoptera: Noctuidae) under different dietary conditions - Yu, Man; Li, Yang; Ji, Jingyuan; Lei, Yonghui; Sun, Yanfei (Frontiers in Microbiology, 2024)
Yeast is one of the important symbiotic flora in the insect gut. However, little is known about the gut yeast in Helicoverpa armigera (Lepidoptera: Noctuidae) under various dietary conditions. The composition and function of the intestinal yeast community also remain unclear. In this research, we explored the composition of yeast microorganisms in H.armigera larvae under different feeding environments, including apple, pear, tomato, artificial diet (laboratory feeding), Urtica fissa, Helianthus annuus, and Zinnia elegans, (wild environment) using high-throughput sequencing. Results showed that a total of 43 yeast OTU readings were obtained, comprising 33 yeast genera and 42 yeast species. The yeast genera with a total content of more than 5% were Hanseniaspora (36.27%), Moesziomyces (21.47%), Trichosporon (16.20%), Wickerhamomyces (12.96%) and Pichia (6.38%). Hanseniaspora was predominant when fed indoors with fruits, whereas Moesziomyces was only detected in the wild group (Urtica fissa, Helianthus annuus, Zinnia elegans) and the artificial diet group. After transferring the larvae from artificial diet to apple, pear and tomato, the composition of intestinal yeast community changed, mainly reflected in the increased relative abundance of Hanseniaspora and the decreased abundance of Trichosporon. Simultaneously, the results of α diversity index indicated that the intestinal yeast microbial diversity of H.armigera fed on wild plants was higher than that of indoor artificial feeding. PCoA and PERMANOVA analysis concluded that there were significant differences in the gut yeast composition of H.armigera larvae on different diets. Our results confirmed that gut yeast communities of H.armigera can be influenced by host diets and may play an important role in host adaptation.